Unnatural Selection: Eugenics and the Spirit World - Gutierrez, Cathy (Studies in religion, 2018)
The religious movement of Spiritualism embraced progress as the hallmark of all existence on earth and in heaven. With the publication of On the Origin of Species, this devotion to improvement fell on difficult moral ground. Many Spiritualists sought to hasten the march of humanity through the intervention of eugenics. Understood as an ethical imperative that would improve the lots of both women and children, the alliance between the eugenics platform and Spiritualists betrayed the unwitting consequences of the politics of progress.